2019
DOI: 10.1049/iet-spr.2018.5258
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epileptic seizure employing a novel set of features extracted from multifractal spectrum of electroencephalogram signals

Abstract: Here, a technique for automated detection of epilepsy is proposed, based on a novel set of features derived from the multifractal spectrum of electroencephalogram (EEG) signals. In fractal geometry, multifractal detrended fluctuation analysis (MDFA) is a technique to examine the self-similarity of a non-linear, chaotic and noisy time series. EEG signals which are representatives of complex human brain dynamics can be effectively characterised by MDFA. Here, EEG signals representing healthy, interictal and seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Among different kernel functions of SVM classifier, the RBF kernel function has been found to deliver better result and hence the performance of the SVM classifier has been evaluated in this study using RBF kernel functions. Mathematically, RBF kernel can be expressed as [22] normalRBF=efalse(γfg2false) where ( f , g ) is a linearly separable training data, and γ=1/2σ2 is the parameter of the RBF kernel and σ is the width. The choice of optimum width σ is particularly important since the performance of the SVM classifier depends on it.…”
Section: Working Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Among different kernel functions of SVM classifier, the RBF kernel function has been found to deliver better result and hence the performance of the SVM classifier has been evaluated in this study using RBF kernel functions. Mathematically, RBF kernel can be expressed as [22] normalRBF=efalse(γfg2false) where ( f , g ) is a linearly separable training data, and γ=1/2σ2 is the parameter of the RBF kernel and σ is the width. The choice of optimum width σ is particularly important since the performance of the SVM classifier depends on it.…”
Section: Working Methodologymentioning
confidence: 99%
“…Among different kernel functions of SVM classifier, the RBF kernel function has been found to deliver better result and hence the performance of the SVM classifier has been evaluated in this study using RBF kernel functions. Mathematically, RBF kernel can be expressed as [22] RBF = e (−g f −g 2 )…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…In the case of multifractal signals, (q) shows non-linear dependency on 'q' and therefore multifractal signals are characterised by multiple Hurst exponents. Applying Legendre transform, the singularity spectrum f(α) is related to the scaling exponent (q) using the following equation [23]:…”
Section: Theory Of Mdfamentioning
confidence: 99%
“…A nonstationary signal can be therefore split into different segments and their scaling behaviour can be studied using different fluctuation functions. Application of the MDFA algorithm to study the dynamic fluctuations of several non-linear and non-stationary signals like partial discharge signals [21], accelerometer signals [22], epileptic seizure EEG signals [23], focal epileptic EEG signals [24] etc. were reported in the available literatures.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions reflect the influence of numerous vital processes. For example, recent studies have shown that many biomedical signals have a multifractal structure [ 12 , 13 , 14 , 15 ]. Such signals represent a complex fractal structure, which cannot be sufficiently characterized by a single summary value (e.g., the Hurst exponent).…”
Section: Introductionmentioning
confidence: 99%